The ethnography of moralities. - Howell, Signe (European Association of Social Anthropologists., 1997)
The social construction of morality is a complex and challenging topic which is central to the anthropological discipline. Until recently, however, it has received little direct attention from anthropologists. With the growing interest in indigenous notions of self and personhood, and related questions regarding human rights, issues pertaining to moral and ethical groundings of social life have become increasingly relevant.So far, however, few anthropologists have concerned themselves with disentangling 'moralities' and how one might set about studying them in empirical settings. The focus for The Enthnography of Moralities was chosen precisely in order to raise a debate around the empirical study of different moral discourses and how these are related to social institutions, to indigenous concepts of human nature (male and female), to cosmology and to the nature of good and evil -- Présentation de l'éditeur.